Tatalaksana Komplikasi Prosedur Laparoskopi pada Pasien dengan Komorbid Obesitas - Sudadi; Saputra, Dya; Pratomo, Bhirowo Yudo (Jurnal Komplikasi Anestesi, 2023)
The main problems with laparoscopy are related to cardiopulmonary effects due to pneumoperitoneum, systemic absorption of carbon dioxide, extraperitoneal gas insufflation, venous gas embolism, injury to intra-abdominal structures and position of the patient, especially in laparoscopic cholecystectomy which is a procedure performed in the upper abdominal region.Therefore the author will discuss the complications of anesthesia in laparoscopic procedures and the management that can be done to prevent and treat these complications. Characteristics of the hemodynamic response begins with a decrease in cardiac index after intraperitoneal insufflation of CO2 gas and is followed by recovery. Compression of the abdominal organs as a result of increased intra-abdominal pressure and increased sympathetic may be one of the causes of increased cardiac filling pressure which can also be associated with increased intrathoracic pressure due to pneumoperitoneum. Insufflation of the intraperitoneal space with CO2 gas produces a pneumoperitoneum, a systemic effect of CO2 absorption and a reflex increase in vagal tone that can develop into arrhythmias